The Impact of Compliance Pressure, Task Complexity, and Auditor Expertise on Audit Judgment - Wirjono, Endang Raino; Fridata, Vinia Filliati (KINERJA, 2023)
This study aims to re-examine previous research on the effect of Compliance Pressure, Task Complexity, and Auditor Expertise on audit judgment but on different objects. The research was conducted in Yogyakarta, Solo, and Semarang, with the respondents being auditors who worked in Yogyakarta, Solo, and Semarang Public Accounting Firms. Data was obtained by distributing questionnaires as many as 50 questionnaires. The number of questionnaires that were returned and processed was 40 questionnaires. Data processing is done using the multiple linear regression method after testing the validity and reliability first. The results showed that task complexity had a negative effect on audit judgment. Meanwhile, compliance pressure and auditor expertise do not affect audit judgment.